Manajemen Pendidikan Islam dalam Perkembangan Sejarah Madrasah di Indonesia - Renata Fifa Aulia; Afina Mazaya Auliya Mida; Naila Wildatun Isnaini (Pusat Riset dan Inovasi Nasional, 2026)
Madrasas as formal Islamic educational institutions in Indonesia have undergone a long evolution from traditional systems to modern institutions that are integrated into the national education system. This study aims to examine the role of Islamic education management in the development of madrasah history using a literature research method with an analytical descriptive approach. The results of the study show that the development of madrassas takes place through several historical phases that are mutually sustainable. In the early 20th century, madrassas emerged in response to the limitations of the traditional pesantren system. In the pre-independence period, the discriminatory policies of the Dutch colonial encouraged the birth of modern madrassas that combined religious and general sciences. Post-independence, the establishment of the Ministry of Religion in 1946 strengthened the position of madrassas in the national education system. During the Old Order period, the number of madrassas increased rapidly even though the management was still community-based. Entering the New Order, the Decree of 3 Ministers of 1975 and Law Number 2 of 1989 encouraged the formal integration of madrasas, although they tended to be centralistic. The Reform Era through Law Number 20 of 2003 provided equal recognition to public schools and encouraged decentralization based on School-Based Management. Although the quantitative and legal development of madrasas is significant, the challenges of quality, funding, and relevance in the era of globalization remain a concern so that madrasas are able to produce graduates who excel intellectually and are solid in Islamic values.